Implementasi Edutainment dalam Pembelajaran Tematik di SD Negeri Banyuwangi 1 Magelang: Penelitian - Anang Amiruddin Nugroho; Tiara Nila Agustina; Dwi Royyand Firdaus Maarif; Subkhani Kusuma Dewi; Aulia Maudy Hasnaning Afifa; Erlina Indrawati; Devita Musyarofah (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Edutainment is a response to the needs of 21st-century learning that emphasizes critical thinking skills, creativity, and digital literacy, through educational games. The purpose of this study was to determine the implementation of edutainment at Banyuwangi 1 Elementary School, Magelang. This study used a descriptive qualitative approach, with data collection techniques through observation, interviews, and documentation. The analysis technique was carried out through data reduction, presentation, and drawing conclusions. The form of verification enrichment of research results through data triangulation. The results of the study showed active involvement of students in the implementation of edutainment in thematic learning. The edutainment model was carried out with ice breaking, experiments, simulations, and practice. Active involvement of students in the implementation of edutainment contributes to the principles of deep learning, namely mindful learning, meaningful learning, and joyful learning.